Is membership in microfinance initiatives associated with viral load suppression among HIV patients? Evidence from western Kenya - Bishnu Bahadur Thapa; Becky Genberg; Juddy Wachira; Jon Steingrimsson; Omar Galarraga (BMC Global and Public Health)
Abstract Background Social and economic factors have considerable influence on the lives of people living with HIV (PLHIV). These factors shape their health behaviors, willingness to engage with other members of their communities for support, and ability to seek appropriate and timely treatment options. Evidence has shown that microfinance initiatives, by providing access to credit and social networks, have the potential to help PLHIV overcome some of these barriers. The objective of this study was to understand the association between microfinance membership and viral load suppression among HIV patients. Methods We used data from the Academic Model Providing Access to Healthcare (AMPATH)-Kenya’s Group Integrated Savings for Health Empowerment (GISHE), a microfinance initiative (MFI), to study the association between GISHE participation and viral load suppression. Our longitudinal dataset consisted of a matched group of 3609 HIV patients. We examined the association between GISHE membership and viral load suppression by addressing the missing data problem with respect to the viral load count via multiple imputation. Results Our study revealed that GISHE membership was associated with increased viral load suppression (adjusted odds ratio (AOR) = 1.15; 95% confidence interval (CI), 1.03–1.29). Further, the study found that male patients were less likely to be virally suppressed (AOR = 0.85; 95% CI, 0.74–0.97), as were the patients in the most advanced disease stage (AOR = 0.71; 95% CI, 0.52–0.95). The finding that GISHE participation was associated with a greater likelihood of viral load suppression held even after addressing the missing data problem. Conclusions We conclude that GISHE-type programs hold promise as scalable interventions to combat HIV/AIDS in Kenya and other countries where the disease is a generalized epidemic.